Corporate social responsibility from the perspective of companies providing express courier services in the Czech Republic - Sommerauerová, Dana; Kučera, Tomáš; Hyršlová, Jaroslava (Oeconomica, 2017)
Corporate social responsibility (CSR) has been lately an extensively discussed topic. CSR has influence on how customers see companies. This concept is important not only for customers, but also for other stakeholders such as are the following: investors, employees, the general public, media, the state and other. With the development of e-commerce social responsibility issues become more and more important for companies providing express courier services. The aim of this paper is to present and to compare approaches taken by the selected companies providing express courier services in the Czech Republic territory to CSR issues.
Společenská odpovědnost z pohledu společností poskytujících expresní kurýrní služby v České republice
Keywords: express courier services; corporate social responsibility; environmental aspects; social aspects; expresní kurýrní služby; společenská odpovědnost podniků; environmentální aspekty; sociální aspekty